2020
DOI: 10.1186/s12876-020-01251-w
|View full text |Cite
|
Sign up to set email alerts
|

The Enhanced Liver Fibrosis test is associated with liver-related outcomes in postmenopausal women with risk factors for liver disease

Abstract: Background: Chronic liver disease (CLD) is usually asymptomatic but earlier detection is critical to permit lifesaving interventions for those at risk due to high alcohol consumption and increased body mass index (BMI). The aim of this study was to estimate the association between the Enhanced Liver Fibrosis (ELF) test and liver-related events (LRE) and its performance in predicting LRE in postmenopausal women with risk factors in a nested case-control study within the United Kingdom Trial of Ovarian Cancer Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“… 47 Another population-based case-control study (n = 173) comprising post-menopausal women with risk factors for liver disease found an AUC of 0.58 for liver-related outcomes. 48 …”
Section: Discussionmentioning
confidence: 99%
“… 47 Another population-based case-control study (n = 173) comprising post-menopausal women with risk factors for liver disease found an AUC of 0.58 for liver-related outcomes. 48 …”
Section: Discussionmentioning
confidence: 99%
“…ELF measures 3 direct markers of liver fibrosis: hyaluronic acid (a glycosaminoglycan that is produced by hepatic stellate cells), PIIINP (a marker of early fibrogenesis and inflammation), and tissue inhibitor of matrix metalloproteinase 1 (the circulating inhibitor of MMP enzymes that can enhance fibrogenesis). Multiple studies have shown that ELF is predictive of hepatic decompensation, liver transplant, liver cancer, and death in chronic liver diseases, [26][27][28] and is superior to fibrosis-4 index, MELD score and Child-Pugh score for predicting the risk of liver-related events. [26] The incidence of hepatic events increased significantly with increased ELF, and lower ELF scores were associated with a reduced risk of liver-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in some clinical investigations, the prevalence of NAFLD was lower in premenopausal women than in men (12.7% vs. 26%), but considerably higher in postmenopausal women than in males of the same age (19.4% vs. 14.9%) (Lonardo et al, 2019;DiStefano, 2020). Furthermore, Trembling et al and Sumida et al confirmed that long-term estrogen deficiency may increase the risk of NAFLD fibrosis in postmenopausal women (Sumida et al, 2020;Trembling et al, 2020). Similarly, the ovariectomized (OVX) rodent models suggest a causal relationship between estrogen deficiency and increased susceptibility to NAFLD (Li et al, 2013;Jeong et al, 2018;Chang et al, 2020).…”
Section: Introductionmentioning
confidence: 98%